Improvement of sulfur compounds in broccoli sprouts by methionine loaded polyvinyl alcohol-sodium alginate hydrogels for application in Kimchi. (January 2020) - Park, Sung Jin; Lee, Min Jung; Choi, Yun-Jeong; Yun, Ye-Rang; Lee, Mi-Ai; Oh, Su Jin; Park, Sung Hee
Abstract: The aim of this study was to increase the sulfur content by developing natural sulfur additives and applying Kimchi. Broccoli sprout was selected as a natural sulfur additives, and sulfur content was improved using a methionine (Met) loaded polyvinyl alcohol (PVA)-sodium alginate (AG) hydrogel (Met-PVA-AG). The optimized Met-PVA-AG exhibited a small particle size (220.63 ± 18.87 nm), a high zeta potential (−37.49 ± 1.29 mV), encapsulation efficiency of methionine (91.91 ± 0.22%), and water content (97.35 ± 1.55%). Additionally, the retention rates of Met (up to 65%) and water (up to 57.18%) were high in Met-PVA-AG stored for 7 days under acidic, neutral and alkaline conditions. The sulfur compound content (sulfur 1607 mg/100 g, sulforaphane 53.12 mg/100 g and glusocinolates 206.79 mg/100 g) of broccoli sprout grown with Met-PVA-AG was higher than broccoli sprouts grown with water and 1% Met solution. The highest antioxidant activity was observed in broccoli sprout grown with Met-PVA-AG in all treatments. To apply sulfur-enriched broccoli sprout in Kimchi, sulfur-enriched broccoli sprouts were coated using a maltodextrin and spray-drying. The coated broccoli sprouts can improve the retention rate of sulfur in Kimchi at 10 °C for 7 day. Highlights: The optimized Met-PVA-AG is an effective hydroponic growth media for broccoli sprout fortified sulfur compounds. The optimized Met-PVA-AG was prepared under the 1% Met: 1% PVA: 1% AG (1:1:1) and 5-cycles HPH (at 10, 000 psi). The effect of Met-PVA-AG on improving sulfur compounds of broccoli sprout was significantly higher than those of water and 1% Met. The maltodextrin coated broccoli sprouts can improve the retention rate of sulfur in Kimchi at 10 °C for 7 day.